Veiling and Unveiling: Trauma in Laura Richards’s “My Japanese Fan” and “Prince Tatters” - Yifah Hadar (European Journal of American Studies)
Lacan explains that the prohibition on incest is the condition of speech. How does incest then manifest in literary texts that portray incest? In other words, can incest have a rhetorical formation as such? No longer able to shelter under the paternal metaphor, suppressed incestuous relations require a different mode of representation found in catachresis, a form of speech that inherently “abuses” the next word for the proper. A Lacanian analysis of Laura Richards’s poems “My Japanese Fan” and “Prince Tatters” shows her recourse to catachresis as a way of confronting the narratives’ destructive consequences, thus rendering the poetic expression of incest on both the semantic and rhetorical levels. Incestuous forces, monstrosity, and loss among them, drive the poetic line to catachrestic landscape. Catachresis as it is manifest in Richards’s two poems can be seen as a mechanism of macrostructure, a dominant whose paradoxical aim is to dismantle the unity suggested by the metaphors as veils. Stripping those metaphors of their fundamentals, Richards signals at a collapse of boundaries, thus offering a glimpse at the abyss of the Real as formulated by Lacan, only to shape them later into a tool of a hesitant cure.